Screen-printed film deposited using quasi 2-dimensional Bi2Se3 nanostructures for desalination membrane filler application. Issue 2 (April 2022) - Kumar, Sushil; Saravanan, M.P.; Kumar, Dileep; Venkatesh, R.
Abstract: Chalcogenides and 2D graphene are the emerging materials being investigated rigorously as efficient membrane filler materials for recovering minerals from seawater and for desalination through recrystallization. In this work quasi-2-dimensional bismuth selenide (Bi2 Se3 ) nanostructure synthesized by microwave-assisted solvothermal method - mixed in ethylene glycol is used as the ink for depositing screen-printed film (SPF). A laboratory-scale experiment univocally demonstrates the possibility of application of SPF as an efficient membrane filler material for desalination processes such as in direct contact membrane distillation (DCMD). Morphology and topography studies confirm the growth of homogeneous hexagonal micro structures with an edge-to-edge length of 20–40 µm with a thickness of 2–3 µm respectively and elemental mapping studies confirm the growth of sodium chloride (NaCl) crystals over the Bi2 Se3 SPF. Growth of different morphology of NaCl (20–40 µm) including the metastable (111) oriented NaCl depicts that Bi2 Se3 film assists the efficient crystallization process and helps in retaining the morphology of NaCl crystals with an enhanced crystal growth rate of the order of 10 −8 –10 −9 m/s. Interestingly, thermoelectric power measurement in these Bi2 Se3 nanostructures with n-type carriers and with Seebeck coefficient value of − 98 μV/K around the room temperature open up a new possibility for a combined desalination membrane filler application along with thermoelectric (TEP) application where the waste heat used for desalination/membrane crystallization can also be harvested in the form of useful electrical energy. Graphical Abstract: ga1 Highlights: Optimization of screen-printed film (SPF) deposited by Bi2 Se3 quasi 2D nanoflakes. Probed by advanced surface characterization like FESEM, elemental mapping and AFM. LSCOM eliminates the background SPF film to decode the exact morphology of NaCl. Proposed as filler material inside the membrane for desalination/recrystallization. Opens up a new gateway for combined desalination and thermoelectric application.